Variation in the Temperature of Local Anaesthetic During Spinal Anaesthesia Influences Shivering in Cesarean Section Patients. Issue 4 (December 2020) - Khan, R.M.; Kaul, N.; Haris, A.; Al Jadidi, A.
Abstract : ( Acta Anaesthesiol Scand . 2020;64:1028)